Merancang Strategi Pemasaran Yang Efektif, Baik Online Maupun Offline Bagi Pelaku UMKM Teh Gambir Kabupaten Pakpak Bharat - Jenny M Simanjuntak; Tri Melda Mei Liana; Krismanto Erick Tobush Naibaho; Vebry M Lumban Gaol (Lembaga Pengembangan Kinerja Dosen, 2026)
Pakpak Bharat Gambir Tea MSMEs are products extracted from the young leaves of the Gambir plant. Not many people know about Gambir tea and its benefits or functions. Gambir tea products can only be found in online marketplaces, such as Tokopedia, Shopee, Lazada, Mbizmarket.co.id, and Indotrading, where Gambir tea producers are registered with the Pakpak Bharat Regency. One local exporter, Agro Lestari, sells